Diseño y promoción de un modelo de desarrollo de turismo comunitario en el sector del Palmar, parroquia La Esperanza, provincia de Cotopaxi. año 2015 - Tapia Andino, Estefanía Vanessa (2016)
Community tourism is one of the modes of tourism that is increasingly aimed at achieving sustainable change is why we are involved directly with nature and protecting it, cultural expressions around us as a commitment to know, admire, enjoy and direct participation in the conservation of natural resources. This thesis will present the different activities that can be developed through community tourism performing designs, different models of promoting community-based tourism activities in the Palmar Complex, which is being driven by the villagers despite empirically all of the powers available in this room.